ANALISIS CLUSTER KABUPATEN/KOTA DI PROVINSI JAWA TIMUR BERDASARKAN LAJU PRODUK DOMESTIK REGIONAL BRUTO DENGAN PENDEKATAN K-MEANS - Ariska Fitriyana Ningrum; Giatma Dwijuna Ahadi (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2022)
Economic growth is one of the macro indicators in economic development. Regional economic growth is influenced by regional conditions and economic potential. Gross Regional Domestic Product (GRDP) is one of the important indicators to determine the economic conditions in a region within a certain period, both on current market prices and constant market prices. Impacted by the pandemic (Covid-19), the economic growth rate of East Java in 2020 drop to -2.33%, grew again by 3.57% in 2021. The industry sectors that decrease during the pandemic is Health Services and Social Activities sector (3.56%); Education Services (2.7%); Information and Communication sector (2.94%). The clustering method is used to classify the sector of GRDP growth rate in District/City of East Java 2021. The Cluster K-Means method is a non-hierarchical clustering algorithm that used to partition data into one or more clusters/groups. Based on the K-Means approach, it is known that the optimal cluster number of District/City grouping in East Java is 2 groups. Cluster 1 is characterized by Districts/Cities that have better economic rate than cluster 2. Districts/Cities in cluster 2 are Probolinggo, Pasuruan, Sidoarjo, Mojokerto, Bangkalan, Kediri City, Malang City, Pasuruan City, Mojokerto City, Madiun City , and Surabaya City.